Do institutions limit clientelism?: A study of the district assemblies common fund in Ghana - Banful, Afua Branoah (International Food Policy Research Institute, 2009)
Analyses of how coveted central-government resources in Africa are shared have shown widespread patronage, ethnic cronyism, and pork-barrel politics. While some governments have attempted to rectify the situation by establishing revenue-sharing formulas, a key unanswered question is whether such institutions are able to achieve this goal. This paper presents an empirical investigation of a pioneering formula-based system of resource allocation from the central government to local governments in Ghana?the District Assemblies Common Fund (DACF). The evidence is consistent with governments being able to politically manipulate resource allocation within the confines of the formula-based system. Nevertheless, this does not suggest that the DACF completely fails to limit political influence. It indicates that other guiding structures of a formula-based system?in particular, how and when the formula can be altered?are important determinants of how well a program such as the DACF is able to resist political pressures.